2022
DOI: 10.3390/jcm11206192
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Women after Deep Endometriosis Surgery: Comparison with Spanish Standardized Values

Abstract: The quality of life (QoL) of women who have been surgically treated for endometriosis may be severely impaired. Therefore, QoL can be a determining factor in the recovery of these patients. The aims of this study were to evaluate if the QoL of women surgically treated for deep endometriosis differs from a healthy age-matched population from Catalonia (Spain) and to analyze the QoL of these women considering concomitant events. This is an observational cross-sectional study, where 112 women (between 18 and 48 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…One study reported a positive correlation between the impairment of HRQoL and age ( 31 ). However, no such correlation was found in another study ( 41 ). Higher HRQoL scores were associated with higher education levels ( 20 ) and status of employment ( 36 ).…”
Section: Resultsmentioning
confidence: 72%
“…One study reported a positive correlation between the impairment of HRQoL and age ( 31 ). However, no such correlation was found in another study ( 41 ). Higher HRQoL scores were associated with higher education levels ( 20 ) and status of employment ( 36 ).…”
Section: Resultsmentioning
confidence: 72%